Evaluation of the activity and substrate specificity of the human SENP family of SUMO proteases - Mendes, A (2016)
Protein modification with the small ubiquitin-like modifier (SUMO) is a reversible process regulating many central biological pathways. The reversibility of SUMOylation is ensured by SUMO proteases many of which belong to the sentrin/SUMO-specific protease (SENP) family. In recent years, many advances have been made in allocating SENPs to specific biological pathways. However, due to difficulties in obtaining recombinant full-length active SENPs for thorough enzymatic characterization, our knowledge on these proteases is still limited. In this work, we used in vitro synthesized full-length human SENPs to perform a side-by-side comparison of their activities and substrate specificities. ProSUMO1/2/3, RanGAP1-SUMO1/2/3 and polySUMO2/3 chains were used as substrates in these analyses. We found that SENP1 is by far the most versatile and active SENP whereas SENP3 stands out as the least active of these enzymes. Finally, a comparison between the activities of full-length SENPs and their catalytic domains suggests that in some cases their non-catalytic regions influence their activity.